2023
DOI: 10.1002/bte2.20230018
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐charging of lithium‐ion batteries: A review of electrolyte design aspects

Abstract: Lithium‐ion batteries (LIBs) with fast‐charging capabilities have the potential to overcome the “range anxiety” issue and drive wider adoption of electric vehicles. The U.S. Advanced Battery Consortium has set a goal of fast charging, which requires charging 80% of the battery's state of charge within 15 min. However, the polarization effects under fast‐charging conditions can lead to electrode structure degradation, electrolyte side reactions, lithium plating, and temperature rise, which are highly linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…270 Aravindan et al review conductive salts used in Li-based batteries. 271 Advances and future directions in the design of electrolytes for fast-charging is provided by Lei et al 272 and Zhang et al . 273 The decomposition of electrolyte components has been the subject to many earlier reviews covering the impact on the SEI 43,46,88,145,274 and CEI.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…270 Aravindan et al review conductive salts used in Li-based batteries. 271 Advances and future directions in the design of electrolytes for fast-charging is provided by Lei et al 272 and Zhang et al . 273 The decomposition of electrolyte components has been the subject to many earlier reviews covering the impact on the SEI 43,46,88,145,274 and CEI.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Numerous publications have demonstrated that the primary challenge in achieving fast charging lies in improving the charging protocol rather than focusing solely on battery chemistry [10]. For example, in the popular Tesla Model 3, manufactured by Tesla, Inc., Austin, TX, USA, the battery can be charged up to an 80% state of charge (S oC ) in less than 30 min, but not without affecting its longevity [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The number of chargers charging vehicle batteries with DC (direct current) with power ranging from 40 to 250 kW is also constantly growing. Currently, the fastest DC chargers have a power of 350 kW and are able to charge electric vehicle batteries in 15 min [29]. Such chargers are usually located at gas stations and passenger service areas located on highways and expressways.…”
Section: Introductionmentioning
confidence: 99%